Communication of Leadership in Da'wah by the Caretaker of TMI Al-Amien Prenduan - Wafiq Azizah Kamila; Agus Saifuddin Amin (Al-Amru: Jurnal Komunikasi dan Dakwah Islam, 2025)
One of the keys to the succes of dakwah is the effectiveness of its leadership. Because only through effective leadership, the dakwah movement can carry out its program to achieve the goals that have been set. Leadership is a process of activity the where  a person moves others by leading, guiding, influencing others, to do something in order to achives the expected result. The focus of the problem in this study is how the communication of the dakwah leadership used by TMI caregiver Al-Amien Prenduan. This study aims to determine the communication of dakwah leadership used by TMI caregiver Al-Amien Prenduan. This research is a research that uses a descriptive field qualitative approach. In this study using data collection techniques through observasion, interview and documentation. The result of this study show that the dakwah leadership communication used by TMI caregivers is using Arisotle’s  communication model and the communication process used is the  process primary. The leadership used by TMI caregivers is more towards the democratic type. And the method of dakwah used by Mauidzah Hasanah. While the dominant form of dakwah is more on bil-oral dakwah.